Performance investigation of using composites in wind turbine airfoils: Review - Nasirinia, Younes; Asgaran, Sohrab; Moazzami Goudarzi, Zahra (Journal of Composites and Compounds, 2025)
The increasing demand for renewable energy, particularly for high-efficiency and lightweight wind turbines, has driven substantial advancements in the application of composite materials for wind turbine structural and airfoil design. This review highlights the role of composites in wind turbine airfoils, focusing on their structural, aerodynamic, and manufacturing performance. It first introduces airfoil geometry and fiber-reinforced composites, including conventional glass and carbon fibers, as well as advanced and hybrid materials. The mechanical, thermal, and fatigue properties of these composites, along with their advantages over metallic materials, are evaluated. Furthermore, the function of composites in commercial turbines and experimental airfoils is discussed, together with challenges such as cost, recyclability, and structural health monitoring. Finally, future trends in composite extend are explored, including convalesce nanomaterials, thermoplastic matrices, and sustainable materials, which are essential for the next generation of high-performance, durable, and environmentally friendly wind turbine airfoils.